Cover Feature: The Influence of UiO‐bpy Skeleton for the Direct Methane‐to‐Methanol Conversion on Cu@UiO‐bpy: Importance of the Encapsulation Effect (ChemCatChem 23/2021). Issue 23 (7th December 2021) - Fu, Lin; Yuan, Min; Li, Xiaodong; Bian, Shuai; Mi, Le; Gao, Zhihua; Shi, Qi; Huang, Wei; Zuo, Zhijun
Abstract : The Cover Feature shows that Cux Ox clusters are confined in the UiO‐bpy skeleton. In their Full Paper, L. Fu, M. Yuan et al. use Cu@UiO‐bpy, which shows high methanol yield and stability in the direct methane‐to‐methanol conversion. Once the UiO‐bpy framework is destroyed, the active sites of small Cux Ox clusters will grow into CuO nanoparticles due to the thermal movement during the reaction. As a result, the catalyst is deactivated. The results show that the encapsulation effect of UiO‐bpy skeleton is the key factor for catalyst stability. More information can be found in the Full Paper by L. Fu, M. Yuan et al.